Effects of post-weld heat treatment on microstructure and mechanical properties of Hastelloy N superalloy welds. (June 2019) - Wang, Wanxia; Jiang, Li; Li, Chaowen; Leng, Bin; Ye, Xiang-Xi; Liu, Renduo; Chen, Shuangjian; Yu, Kun; Li, Zhijun; Zhou, Xingtai
Abstract: The effects of post-weld heat treatment (PWHT) on the microstructure and mechanical properties of Hastelloy N superalloy welds were systematically investigated. Eutectic-like M6 C carbides and nano-sized M2 C carbides were observed in the interdendritic region of the as-welded specimens, with finer granular M6 C carbides precipitating at the dendrite boundaries. With the increase in the PWHT temperature, the nano-sized M2 C carbides dissolved, while the M6 C carbides at the dendrite boundaries coarsened. When the PWHT temperature increased to 950 °C, the nano-sized M2 C carbides completely disappeared. Consequently, the weld with the PWHT at higher temperatures exhibited lower micro-hardness, lower yield strength, and higher elongation. In particular, the elongation increased by 63% after applying the PWHT at 950 °C for 6 h.